PENGARUH CASH CONVERSION CYCLE, LIKUIDITAS DAN FIRM SIZE TERHADAP PROFITABILITAS - Ni Luh Putu Widya Giriyani; Lucia Ari Diyani (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
This study aims to measure how influential the cash conversion cycle (consisting of average age of inventory, average collection period and average payment period), liquidity (proxied by current ratio) and firm size of profitability (proxied by return on assets). The object of this research is consumer goods industry with research period 2012-2016. The samples of companies used in this study are six companies that have passed the criteria that have been determined in purposive sampling. The results of research that has been done through the application of IBM SPSS 23 then it can be concluded cash conversion cycle, liquidity and firm size affect simultaneously to profitability. In addition, the test partially explains that the average age of inventory, the average collection period and firm size negatively affect return on assets while the average collection period and current ratio has no effect on return on assets.